Self-Training and Research from Practice: A Study with Postgraduate Alumni - Bermejo-Paredes, Saúl (2025)
Introduction. In universities, postgraduate alumni may theoretically demonstrate exceptional research skills; however, in practice, they generally conduct basic research. Those who hold the greatest number of academic publications are rewarded, without considering their potential contribution to problem solving or the impact on the perceived value of academic integrity. Objective. To analyze the relationship between research capabilities and attitudes in postgraduate alumni to propose innovative, experience-based, and self-reflective processes of practical self-directed learning. Methodology. The study was conducted with a convenience sample of 53 postgraduate students and graduates (master’s and doctoral levels) from two Peruvian universities. It employed a quantitative-qualitative methodology approach, with a descriptive-explanatory and phenomenological-interpretive design. Data were collected through a semi-structured interview and a questionnaire, whose reliability test yielded a Cronbach’s alpha coefficient of 0.843. Results. No significant relationship was found between the development of research capacities and attitudes (r = 0.028, and bilateral significance level of 0.844). Scientific research is predominantly conceived as a methodological matter and unilateral review-correction process, subordinated to schemes, regulations and deep-rooted beliefs among academic actors. Discussion and conclusion. There is a need to reinvent research training and practice by adopting a collaborative approach (where everyone learns and everyone teaches) and self-directed, reflective, and constructive learning processes of timely interaction between authors and reviewers to assess successes, failures, and pending challenges, seeking strategies for collaboration, self-awareness, motivation, and accountability to achieve positive impact and scientific productivity. It is advisable to reconsider organizational frameworks, paradigms, and the roles of those involved in research processes.